Designing Superhydrophilic 3D Porous Surfaces on Polyetherketoneketone Surfaces to Promote Biocompatibility - Hui-Ching Lin; Chiang-Sang Chen; Kai-Yi Lin; Ya-Lin Huang; Hao-Hsiang Hsu; Yu-Lin Kuo; Wei-Cheng Chen; Her-Hsiung Huang (Journal of Functional Biomaterials)
Polyetherketoneketone (PEKK) exhibits satisfactory mechanical properties and biocompatibility, with an elastic modulus closely resembling that of natural bone. This property reduces the stress-shielding effect associated with bone implants. However, the biological inertness of the PEKK surface remains a significant limitation for its application in bone tissue engineering. The objective of this study was to create a superhydrophilic 3D porous structure on the surface of PEKK to enhance biocompatibility, in terms of vascularization and bone remodeling. A combination of mechanical, chemical, and physical surface treatments was employed to modify the PEKK surface. Initially, mechanical sandblasting was used to create a rough surface to promote mechanical interlocking with bone tissue. Subsequently, chemical acid etching and physical low-temperature atmospheric plasma cleaning were applied to develop a superhydrophilic 3D porous surface. The modified surfaces were characterized for morphology, roughness, hydrophilicity, and functional groups. Cellular responses, including vascularization and bone remodeling, were evaluated to assess the potential for improved biocompatibility. The combination of acid etching and low-temperature atmospheric plasma cleaning, with or without prior sandblasting, successfully created a superhydrophilic 3D porous structure on the PEKK surface. This modified surface enhanced the tube formation in human umbilical vein endothelial cells. It also promoted the adhesion and mineralization of human bone marrow mesenchymal stem cells and slightly reduced tartrate-resistant acid phosphatase expression and F-actin ring size in mouse macrophage cells. This study introduces an innovative and effective surface modification strategy for PEKK surface, combining mechanical, chemical, and physical treatments to enhance biocompatibility. The modified PEKK surface promotes angiogenic and osteogenic responses while slightly inhibiting osteoclastic activity, making it a potential alternative for dental and orthopedic PEKK implant applications.